2010
DOI: 10.1007/s10755-010-9139-7
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy for Equity: Teaching in a Hispanic-Serving Institution

Abstract: Three female tenure-track faculty members at a Hispanic-Serving Institution explored how their cultural backgrounds inform their pedagogical approaches toward equity. They drew upon Mills's (1959) and Collins's (1993) frameworks to examine how their personal biographies, local social contexts, and broader systemic institutions affect their teaching processes for diverse students. These teaching processes include limiting assumptions about students, encouraging students to consider their own personal biographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 21 publications
(22 reference statements)
1
43
0
Order By: Relevance
“…Some HSIs incorporate advising models that are culturally relevant (Garcia & Okhidoi, 2015) while others enact student support programs that validate Latinx students (Martinez & Gonzales, 2015). There are also numerous examples of faculty at HSIs that utilize culturally relevant pedagogy in their classrooms, recognizing the unique ways of knowing of Latinx students (Cervantes, 2015;Kiasatpour & Lasley, 2008;Lara & Lara, 2012;Núñez, Murakami-Ramalho, & Cuero, 2010). Alternatively, some studies have revealed that the way that Latinxs experience the campus culture at HSIs is complex (i.e., sometimes positive and sometimes negative) (Cuellar & Johnson-Ahorlu, 2016;Garcia, 2015), further complicating the argument about the extent to which HSIs are effectively serving Latinx students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some HSIs incorporate advising models that are culturally relevant (Garcia & Okhidoi, 2015) while others enact student support programs that validate Latinx students (Martinez & Gonzales, 2015). There are also numerous examples of faculty at HSIs that utilize culturally relevant pedagogy in their classrooms, recognizing the unique ways of knowing of Latinx students (Cervantes, 2015;Kiasatpour & Lasley, 2008;Lara & Lara, 2012;Núñez, Murakami-Ramalho, & Cuero, 2010). Alternatively, some studies have revealed that the way that Latinxs experience the campus culture at HSIs is complex (i.e., sometimes positive and sometimes negative) (Cuellar & Johnson-Ahorlu, 2016;Garcia, 2015), further complicating the argument about the extent to which HSIs are effectively serving Latinx students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers call upon HSIs to provide Latina/o students with the academic capital to be culturally informed to serve families, communities, schools, and businesses in an ever-changing social, cultural, economic, and transnational environment (García, 2012;Gonzales, 2016;Núñez et al, 2010). Within a short time of operation, UTRGV is cultivating and expanding students'…”
Section: Resultsmentioning
confidence: 99%
“…This research offers recommendations regarding what works for Latina/o students to achieve academic success and facilitates the process of changing higher education to serve these students more appropriately and responsibly (Evans, 2009;Hagedorn et al, 2007;Greene et al, 2012;Núñez et al, 2010;Núñez, Crisp, & Elizondo, 2016;Verdugo, 1995). These recommendations are divided into two categories-life worlds and systems worlds.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations